2018
DOI: 10.1111/pace.13521
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial volume, estimated using magnetic resonance imaging, predicts atrial fibrillation recurrence after ablation

Abstract: Introduction:The predictive value of left atrial volume (LAV) in atrial fibrillation (AF) is known, but the relationship of right atrial volume (RAV) and biatrial volume (BAV) with AF recurrence after pulmonary vein isolation (PVI) is not clear. Cardiac magnetic resonance (CMR) imaging allows us to more precisely quantify atrial volume. We investigated LAV, RAV, and BAV as predictors of AF recurrence following PVI in AF patients. Methods and Results:We assessed 100 AF patients (age = 59.8 ± 9.5 years, 74 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Those undergoing hemodialysis with new-onset AF exhibit heightened risks of death and stroke [23], and chronic kidney disease and hemodialysis impact mortality, length of stay, and total cost of hospitalization in patients admitted with a primary diagnosis of paroxysmal AF [24]. Furthermore, the biatrial volume predicts AF recurrence after ablation, impacting mortality [25].…”
Section: Resultsmentioning
confidence: 99%
“…Those undergoing hemodialysis with new-onset AF exhibit heightened risks of death and stroke [23], and chronic kidney disease and hemodialysis impact mortality, length of stay, and total cost of hospitalization in patients admitted with a primary diagnosis of paroxysmal AF [24]. Furthermore, the biatrial volume predicts AF recurrence after ablation, impacting mortality [25].…”
Section: Resultsmentioning
confidence: 99%
“…It was independently linked to a higher risk of heart failure, cerebrovascular events, and mortality in a single-center study involving 254 subjects with non-valvular AF [ 34 ]. A study based on cardiac MRI, which included patients undergoing pulmonary vein isolation, showed that all three atrial volumes (left, right, and bi-atrial) were significantly correlated with AF recurrence after ablation, but the bi-atrial volume presented the highest AUC value for risk prediction in this context [ 35 ]. This is similar to our results, where we found significant prognostic capacity for all indexed volumes, but the bi-atrial indexed volume presented the largest area under the curve compared with LAVI or RAVI alone.…”
Section: Discussionmentioning
confidence: 99%
“…[ 64 ] demonstrated that LA volume, as determined by preoperative cardiovascular MRI, is a powerful predictor of AF recurrence after CA. Further studies have shown that, in addition to LA volume, RA volume and biatrial volume quantified by MRI can also predict AF recurrence after CA [ 65 ]. Alternatively, LA shape has been found to provide prognostic information for CA treatment [ 14 , 66 ].…”
Section: Use Of Mri For the Prediction Of Af Recurrence After Camentioning
confidence: 99%
“…A summary of studies that used MRI to predict recurrence after CA in patients with AF is presented in Table 3 (Ref. [ 13 , 14 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 72 , 74 , 75 , 77 , 78 , 79 ]). Fig.…”
Section: Use Of Mri For the Prediction Of Af Recurrence After Camentioning
confidence: 99%